Beyond the campus: the development of social emotional competence in freshmen through a community-based eldercare volunteer service project - Lyu, Keyi; Lin, Hanxiao; Zhu, Danlei (Frontiers in Psychology, 2025)
Enhancing social emotional competence for freshmen is crucial for their successful integration into diverse university and social environments. While existing research mainly focused on the impact of specific social emotional learning courses on freshmen, there has been limited exploration of the influence of social practice participation. This study investigates the impact of intergenerational volunteer service on freshmen's SEC growth through a collaborative project between H University and G Community from October to December 2024. Through semi-structured interviews with thirteen first-year student volunteers who participated in this project, the findings indicate that participation significantly enhanced freshmen's SEC in five key areas: (1) broaden students' perspectives on university life, (2) reduce study-related anxiety, (3) strengthen social connections and social awareness, (4) promote altruistic behavior and responsible decision-making, and (5) enhance self-confidence and self-efficacy. The results highlight that SEC development is an interactive process involving cognition, behavior, and emotion. Furthermore, eldercare communities can serve as unique informal learning spaces.